HUBUNGAN PENGETAHUAN TENTANG KESEHATAN REPRODUKSI DAN PERAN ORANG TUA DENGAN PERILAKU SEKSUAL PADA REMAJA SISWA KELAS VIII SMP GAJAH MADA MEDAN SELAYANG TAHUN 2024 - Devi Malinda Nuryantina; Elvipson Sinaga (STIKES Columbia Asia Medan, 2024)
Sexual behavior among teenagers in class VIII of Gajah Mada Middle School, Medan Selayang, many of them engage in sexual behavior. Sexual behavior in adolescent students of class VIII SMP Gajah Mada Medan Selayang is related to knowledge about reproductive health and the role of parents in sexual behavior. The aim of this research is to determine the relationship between knowledge about reproductive health and the role of parents with sexual behavior among adolescent students in class VIII of SMP Medan Selayang in 2024. This type of research is descriptive analytical survey research with a research plan (cross sectional study). The population in this study were all teenagers in class VIII of SMP Gajah Mada Medan Selayang, totaling 50 students and a sample of 50 respondents. This data collection technique uses primary and secondary data. This data was analyzed using the chi square test with a knowledge level of 95%. The results of this research are that there is a relationship between knowledge about reproductive health and the role of parents and there is a relationship between sexual behavior in teenagers in class VIII of Gajah Mada Middle School Medan Selayang in 2024, that the more knowledge teenagers have can reduce sexual behavior in teenagers based on the results of the chisquare statistical test using The SPSS application obtained a p-value = 0.000, thus, p-value (0.000) <0.05. A meaningful conclusion can be stated that the knowledge and role of parents regarding sexual behavior has an influence on teenagers because teenagers who have good knowledge will make it easier for teenagers to get information about healthy sexual behavior.